Project Spraoi: Dietary Intake, Nutritional Knowledge, Cardiorespiratory Fitness and Health Markers of Irish Primary School Children - Merrotsy, A.; McCarthy, A.L.; Flack, J.; Lacey, S.; Coppinger, T (International Journal of Child Health and Nutrition, 2018)
Objective: Examine dietary intake (DI), anthropometric measures, cardiorespiratory fitness (CRF) and nutritional knowledge (NK) of school children. Design: Cross-sectional study. Food Diary, NK questionnaire and 550m walk/run test were used to assess DI, NK and CRF respectively. Blood pressure (BP) was also taken and body mass index (BMI) and waist to height ratio (WHtR) were calculated. Setting: Two primary schools, Cork, Ireland. Subjects: Six (n = 49, age 5.9 ± 0.6 years) and ten (n = 52, age 9.8 ± 0.5 years) year olds. Results: Intakes of fruit and vegetables, fibre, calcium and iron were sub-optimal. Unhealthy snacks and saturated fat intakes were higher than recommended. A total of 24.4% of six year olds and 35.4% of ten year olds were classified as ‘fast’. Furthermore, 45.9% of six and ten year olds had high-normal BP and 27.9% had high BP. NK was negatively correlated with sugar intake (r = -0.321, p = 0.044) in ten year olds. WHtR was negatively correlated with servings of vegetables in six year olds (r = -0.377, p = 0.014). For ten year olds, there was a positive correlation between WHtR and run score (r = 0.350, p = 0.014) and BMI and run score (r = 0.482, p = 0.001). Conclusion: This study highlights, for the first time, DI, NK, CRF, BP and anthropometric data for Irish children and their potential combined effect on overall health. Study results suggest preventive initiatives are needed, in children as young as 6 years of age.